No Longer Invisible: families that Torture, Traffic, and Exploit their Girl Child - Sarson, Jeanne (Oñati Socio-Legal Series, 2018)
This paper discusses non-State torture families that organize the sexualized trafficking and exploitation of their girl child to their network of like-minded individuals and groups. They have eluded being identified in the extensive research that informs the Global Report on Trafficking in Persons (2014) by the United Nations Office on Drugs and Crime. This means the trafficked and tortured girl child has been absent from the profile of trafficked children. Understanding the girl child’s position of vulnerability and complex relational victimization and traumatisation responses to being tortured, trafficked, and exploited is essential to recommending interventions that address socio-legal and knowledge gaps and promote the dignity and human rights of the girl child.